A Spatial Analysis of Serotine Bat (Eptesicus serotinus) Roost Location and Landscape Structure: A Case Study in Sussex, UK. (29th December 2013) - Tink, Michael; Burnside, Niall G.; Waite, Stephen
Abstract : Roost location is a key factor affecting the survival and fitness of British bats. It has been suggested that a knowledge and understanding of the factors which may influence the selection of roost location are fundamental to conservation efforts. Our study aims to investigate the relationship between Eptesicus serotinus roost location and landscape structure. The study is based in the Sussex region of South East England. The landscape characteristics of 97 roosts locations were compared against 100 random control locations. Habitat analysis was carried out at three distance bands and included an analysis of roost density. The results indicate that E. serotinus is selective in locating roosts. The study demonstrates that there are significant differences between the landscape composition surrounding roost sites and the wider landscape. In particular, E. serotinus roost sites are found to be located in areas with a significantly higher cover of arable land and improved grassland. Kernel density analysis was successfully used as an additional method to the direct comparison of roost neighbourhood composition. Density analysis identified the location and characteristics of possible centres of E. serotinus activity. It is anticipated that the findings will enable the needs of bats to be considered in future landscape conservation initiatives and development policies.